If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9d + -1 = -6d + -31 Reorder the terms: -1 + 9d = -6d + -31 Reorder the terms: -1 + 9d = -31 + -6d Solving -1 + 9d = -31 + -6d Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '6d' to each side of the equation. -1 + 9d + 6d = -31 + -6d + 6d Combine like terms: 9d + 6d = 15d -1 + 15d = -31 + -6d + 6d Combine like terms: -6d + 6d = 0 -1 + 15d = -31 + 0 -1 + 15d = -31 Add '1' to each side of the equation. -1 + 1 + 15d = -31 + 1 Combine like terms: -1 + 1 = 0 0 + 15d = -31 + 1 15d = -31 + 1 Combine like terms: -31 + 1 = -30 15d = -30 Divide each side by '15'. d = -2 Simplifying d = -2
| 12n+13= | | 7q=15+11q-3 | | -5m-24=m | | 3x-1=7+x | | y=2+lnx | | X+870=2x+870+8570-14150 | | x(3)+x-4(1.50)+4(1.50)=55.80 | | 3(2x-4)=20(5-3x) | | 3(x-2)=10(5-3x) | | 2x+870+8570=2x+870+8570+14150 | | (3x-1)+(y+5)i=1-3i | | 3x+y+5*4i=2 | | 10(d+4)=40 | | 12-(4x-3)=30 | | 32=17 | | 3(2y-7)=9 | | 6-9x=-3 | | -(x-9)=-x-9 | | -(x-7)=-x-7 | | 3x-(5x-(105-30x)-35)=12 | | 8x+16=56-2x | | lg(2x)=-1 | | 24=8x+6y | | 9-4y=-5y | | 41+13x=37+8x+8 | | 0,1x-10=30 | | 5(3w+7)=-32 | | X^2=1.93 | | 4534543534534+4353434534= | | x(x-5)=176 | | (x-5)(x+4)=(x+7)(x-6) | | 3w+7=-6.4 |